Auditory P300 event-related potential and acoustic features of voice and speech in adolescents at risk for suicide: A pilot study - Figueroa Saavedra, Carla; Huenupán Quinán, Fernando; Guillén Cañas, Virginia; Méndez Bustos, Pablo; Alarcón Acuña, Enzo; Pérez, Hernán Emilio (Journal of neurolinguistics, 2026)
Suicide remains a leading cause of external mortality, posing a significant yet preventable challenge. This study explores potential associations between suicide risk and neurophysiological (Auditory P300 Event-Related Potential) and acoustic voice and speech parameters in adolescents. The study employed a cross-sectional design. Thirty secondary school students underwent auditory assessment, P300 measurement (PEATS Eclipse EP25), and acoustic analysis of voice and speech. Suicide risk was determined using the Okasha Suicidality Scale and the Beck Depression Inventory. Acoustic analysis was performed using Praat software for phonetic research, a Focusrite Scarlett interface, and a condenser microphone to assess fundamental frequency (F0), jitter, shimmer, and formants (F1, F2, F3). Data were analyzed using IBM SPSS Statistics version 26.0 and MATLAB R2022a (MathWorks Inc.) for signal processing and feature extraction, applying both descriptive and inferential statistical methods. Adolescents at risk for suicide exhibited significantly longer P300 latencies in both ears compared to their non-risk peers (p < 0.05), while no significant differences were observed in P300 amplitude. Regarding voice analysis, significant group differences were found in the F1, F2, and F3 formants during the open-ended question task (p < 0.05), suggesting alterations in speech articulation. However, vowel production parameters did not differ notably between groups. Adolescents at risk for suicide demonstrated delayed neurophysiological processing (increased P300 latency) and altered speech articulation during spontaneous speech tasks. These findings highlight the potential of integrating P300 and acoustic analysis of voice and speech as complementary markers in assessing cognitive and emotional functioning in suicide risk detection. •P300 latency was longer in adolescents at suicidal risk.•Voice formants differed in spontaneous emotional speech tasks.•No amplitude differences were found in P300 responses.•Combined P300 and voice features improved risk classification.